Factors influencing the adoption of the sentinel lymph node technique for endometrial cancer staging: an international survey of gynecologic oncologists - Casarin, Jvan; Multinu, Francesco; Abu-Rustum, Nadeem; Cibula, David; Cliby, William A; Ghezzi, Fabio; Leitao, Mario; Konishi, Ikuo; Nam, Joo-Hyun; Querleu, Denis; Soliman, Pamela T; Yost, Kathleen J; et al. (International journal of gynecological cancer, 2019)
OBJECTIVE: To explore the factors influencing adoption of the sentinel lymph node (SLN) technique for endometrial cancer staging among gynecologic oncologists. METHODS: A self-administered, web-based survey was sent via email (April 20 through May 21, 2017) to all members of European Society of Gynecologic Oncologists, International Gynecologic Cancer Society, and Society of Gynecologic Oncologists. Surgical and pathologic practices related to SLN and reasons for not adopting this technique were investigated. RESULTS: Overall, 489 attending physicians or consultants in gynecologic oncology from 69 countries responded: 201 (41.1%), 118 (24.1%), and 117 (23.9%) from Europe, the USA, and other countries, respectively (10.8% did not report a country). SLN was adopted by 246 (50.3%) respondents, with 93.1% injecting the cervix and 62.6 % using indocyanine green dye. The National Comprehensive Cancer Network SLN algorithm was followed by 160 (65.0%) respondents (USA 74.4%, Europe 55.4%, other countries 71.4%). However, 66.7% completed a backup lymphadenectomy in high-risk patients. When SLN biopsy revealed isolated tumor cells, 13.8% of respondents recommended adjuvant therapy. This percentage increased to 52% if micrometastases were detected. Among the 243 not adopting SLN, 50.2% cited lack of evidence and 45.3% stated that inadequate instrumentation fueled their decisions. CONCLUSIONS: SLN with a cervical injection is gaining widespread acceptance for staging of endometrial cancer among gynecologic oncologists worldwide. Standardization of the surgical approach with the National Comprehensive Care Network algorithm is applied by most users. Management of isolated tumor cells and the role of backup lymphadenectomy for 'high-risk' cases remain areas of investigation.
Keywords: Oncologists; endometrial cancer; Lymph Node Excision; Female; sentinel lymph node; Sentinel Lymph Node; Sentinel Lymph Node Biopsy; survey; indokyanová zeleň; biopsie sentinelové lymfatické uzliny; onkologové; sentinelová uzlina; ženské pohlaví; Surveys and Questionnaires; lymphadenectomy; minimally invasive surgery; průzkumy a dotazníky; lymfadenektomie; Gynecology; nádory endometria; Indocyanine Green; Endometrial Neoplasms; gynekologie; lidé; Humans